Trace elements, macro minerals and iron forms content, in meat of Pampa Rocha pig reared indoor and outdoor with pasture - Carballo, Cecilia; Espino, Nandy; Vodanovich, Ana; Ferrando, Marcelo; Saadoun, Ali; Cabrera, María Cristina (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Pampa Rocha pig (PRp) is a local breed present and produced in Uruguay. Twenty-three pigs were used housed indoor (I) and outdoor with pasture (O), live weight 94.5 and 91.5 kilograms (kg), respectively. Animals were fed with concentrate in both systems, but pasture access was granted to the animals in the O. After slaughtering, the Longissimus dorsi (LD), Psoas major (PM), Gluteus medius (GM), Semitendinosus (ST), Biceps femoral (BF), and Quadriceps femoris (QF) were sampled to be analyzed. In O, the growth of pigs was lower, and improved the concentrate intake:live weight gain. The content of heme iron and the ratio Fe Heme/Fe Total were higher in outdoor. The LD muscle showed lower total and heme iron content. For ham, QF showed the highest values of heme iron. No differences were observed between systems or muscles in the content of Ca, Mg, and K. The Na content was similar in both systems, and higher in PM. No differences were observed between production systems for trace elements content. According to the results obtained, it is possible to produce PRp meat with interesting mineral content, in two alternative systems to the classic confinement. This breed produces healthier meat in O. It could be interesting to exploit some differences founded between LD and PM muscles, which are normally consumed as fresh meat, and are adapted to the different demands of human nutrition. Rearing in O that include pastures is a good way to promote and add nutritional value to this local breed.